STRATEGI PEMERINTAH DESA KWANGSAN KECAMATAN SEDATI KABUPATEN SIDOARJO DALAM MENINGKATKAN INDEKS KETAHANAN SOSIAL (IKS) PADA STATUS DESA MANDIRI - Vika Armelya Putri; Trenda Aktiva Oktariyanda; Meirinawati; Eva Hany Fanida (Publika, 2026)
The implementation of strategic management in improving the Social Resilience Index (Indeks Ketahanan Sosial/IKS) represents an effort by village governments to strengthen social cohesion and community stability amid social dynamics and modernization. The Government of Kwangsan Village has implemented strategies to enhance social resilience through community participation and public service innovation. This study aims to analyze the strategic management process of Kwangsan Village Government in improving the Social Resilience Index by applying the strategic management framework proposed by Ahmad (2020) and the strategy evaluation perspective of David & David (2017), which includes strategy formulation, implementation, and evaluation. This research employed a descriptive qualitative approach. Data were collected through interviews, observation, and documentation. The informants consisted of village officials and community members. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that strategic management in Kwangsan Village has been implemented in a progressive and adaptive manner. In the formulation stage, the village government identified internal strengths such as social capital and institutional capacity, as well as challenges including declining participation in several IKS indicators. Strategy implementation was carried out through strengthening social activities and digital-based public service innovations. Strategy evaluation was conducted through program review and adjustment of approaches; however, it has not been fully supported by systematically documented and measurable performance indicators.